2014
DOI: 10.3109/03008207.2014.941106
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of siRNA targeting PPARγ gene on steroid-induced osteonecrosis in rabbits

Abstract: Purposes/Aim: Glucocorticoid steroids can induce expression of PPARg gene and enhance adipogenesis by bone marrow mesenchymal stem cells (BMSCs), which may result in osteonecrosis of the femoral head. Currently, there are no medications available to prevent steroid-induced osteonecrosis. We hypothesized that siRNA targeting PPARg gene may prevent steroid-induced adipogenesis and osteonecrosis in rabbit. The purpose of this study was to evaluate the preventive effects of siRNA targeting PPARg gene on steroid-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Intramedullary fat deposition is revealed as a critical pathological feature in the progress of ONFH, characterized by enlarged cellular size and increased number of adipocytes . The strengthened capacity of adipogenesis in ethanol‐induced ONFH has been revealed in several animal models . Notably, promoted adipogenic differentiation led to disordered osteogenic differentiation, and the accumulation of adipocytes might lead to a high intramedullary pressure and impair brittle blood circulation in the femoral heads .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intramedullary fat deposition is revealed as a critical pathological feature in the progress of ONFH, characterized by enlarged cellular size and increased number of adipocytes . The strengthened capacity of adipogenesis in ethanol‐induced ONFH has been revealed in several animal models . Notably, promoted adipogenic differentiation led to disordered osteogenic differentiation, and the accumulation of adipocytes might lead to a high intramedullary pressure and impair brittle blood circulation in the femoral heads .…”
Section: Discussionmentioning
confidence: 99%
“…The strengthened capacity of adipogenesis in ethanol‐induced ONFH has been revealed in several animal models . Notably, promoted adipogenic differentiation led to disordered osteogenic differentiation, and the accumulation of adipocytes might lead to a high intramedullary pressure and impair brittle blood circulation in the femoral heads . Moreover, fat emboli in vessels and sinusoids can also indirectly induce intravascular coagulation via the complement signalling pathways and deposition of immune complex, whereas antithrombotic reagents have protective effects to promote circulation and ameliorate ONFH .…”
Section: Discussionmentioning
confidence: 99%
“…Many mechanisms for the pathogenesis of SONFH have been proposed, but no consensus yet exists as to the exact mechanism. Glucocorticoids directly inhibit differentiation of osteogenic progenitors to osteoblasts while simultaneously promoting adipocyte formation and deposition [8][9][10]. Liu et al [8] found that impaired osteogenic differentiation associated with connexin43/microRNA-206 is implicated in SONFH.…”
Section: Rabbitmentioning
confidence: 99%
“…Fan et al [9] found that hypoxia inducible factor prolyl hydroxylase inhibitor prevents SONFH in rabbits by promoting angiogenesis and inhibiting apoptosis. Li et al [10] found that small interfering RNA (siRNA) that targets the PPARγ gene inhibits adipocytic differentiation of bone marrow mesenchymal stems cells (BMSCs) and prevents SONFH in rabbits.…”
Section: Rabbitmentioning
confidence: 99%
“…Hypoxia and ischemia cause damage to the mitochondrial function, increased oxygen free radicals, and decrease the activity of the ATP synthetase (26). The ATP synthetase on the cytomembrane surface is highly ectopic (27) in the intermediate and advanced stages. It participates in the repair process through a certain negative feedback mechanism and signal transduction.…”
Section: Discussionmentioning
confidence: 99%